2013
DOI: 10.1017/s1368980013003078
|View full text |Cite
|
Sign up to set email alerts
|

Health-related claims on food labels in Australia: understanding environmental health officers’ roles and implications for policy

Abstract: Objective: Health and related claims on food labels can support consumer education initiatives that encourage purchase of healthier foods. A new food Standard

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In Australia and New Zealand, the use of claims is voluntary, and for most claims, the wording is not prescribed, which may contribute to the perception that nutrition and health claims are unregulated (Riley et al, 2016). Enforcement of the Code and compliance monitoring of on-pack claims is currently the role of the state and territory authorities, however previous research has found that the jurisdictions neither have the capability or capacity to monitor compliance with the Code (Condon-Paoloni et al, 2015). Potential solutions to address this issue may be for FSANZ to adopt a more regulatory role in relation to the Code to alleviate the burden on the jurisdictions and improve compliance with the Code or for FSANZ to assist food manufacturers in the interpretation of Standard 1.2.7 so that claims are more compliant with the code before entering the market, as suggested by Wellard-Cole et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia and New Zealand, the use of claims is voluntary, and for most claims, the wording is not prescribed, which may contribute to the perception that nutrition and health claims are unregulated (Riley et al, 2016). Enforcement of the Code and compliance monitoring of on-pack claims is currently the role of the state and territory authorities, however previous research has found that the jurisdictions neither have the capability or capacity to monitor compliance with the Code (Condon-Paoloni et al, 2015). Potential solutions to address this issue may be for FSANZ to adopt a more regulatory role in relation to the Code to alleviate the burden on the jurisdictions and improve compliance with the Code or for FSANZ to assist food manufacturers in the interpretation of Standard 1.2.7 so that claims are more compliant with the code before entering the market, as suggested by Wellard-Cole et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…These adequate resources are required through all stages of research activity; therefore, MSEs poorly conduct these resources-intensive activities. Interconnection policies like stakeholders, government, financial institutions, and universities can improve the capacity of the MSE's production in food health-related claims with the minimum production cost (Purwaningsih and Hardiyati 2021;Condon-Paoloni et al 2015).…”
Section: Compliance Level Of the Prohibited Statement On The Labelmentioning
confidence: 99%
“…The current system relies on state and local government enforcement agencies being adequately resourced to assess the industry-provided dossiers of evidence to decide whether there is sufficient, good-quality evidence for the food company to make the claim. However, enforcement agencies may not have the time to enforce all food labelling issues, or the necessary skills to assess the evidence, or they may prioritise other food regulatory issues over health claims ( 24 ) . Therefore, the food industry can potentially make claims based on poor-quality research if no complaints are received.…”
mentioning
confidence: 99%